Context-Aware Systems and Applications Second International Conference, ICCASA 2013, Phu Quoc Island, Vietnam, November 25-26, 2013, Revised Selected Papers - Vinh, Phan Cong; Alagar, Vangalur; Vassev, Emil; Khare, Ashish (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed proceedings of the Second International Conference on Context-Aware Systems and Applications, ICCASA 2013, held in Phu Quoc Island, Vietnam in November 2013. The 36 revised full papers presented were carefully selected and reviewed from over 100 submissions and cover a wide spectrum of issues in the area of context-aware systems (CAS) and context-based recommendation systems.